2015 IEEE International Conference on Computer Vision Workshop (ICCVW) 2015
DOI: 10.1109/iccvw.2015.142
|View full text |Cite
|
Sign up to set email alerts
|

Fast Structure from Motion for Sequential and Wide Area Motion Imagery

Abstract: We present a fast and efficient Structure-from-Motion (SfM) pipeline for refinement of camera parameters and 3D scene reconstruction given initial noisy camera metadata measurements. Examples include aerial Wide Area Motion Imagery (WAMI) which is typically acquired in a circular trajectory and other sequentially ordered multiview stereo imagery like Middlebury [46], Fountain [50] or body-worn videos [27]. Image frames are assumed (partially) ordered with approximate camera position and orientation informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Computing homographies for even small crop fields can be very challenging, and both approaches have additional difficulties when compared with mosaicking man‐made built environments (AliAkbarpour et al, 2015, 2017). First, built environments have many unique, sharp‐edged features that remain static during image capture and are minimally repeated over the landscape of interest, enabling the use of edge‐detection algorithms.…”
Section: Figurementioning
confidence: 99%
“…Computing homographies for even small crop fields can be very challenging, and both approaches have additional difficulties when compared with mosaicking man‐made built environments (AliAkbarpour et al, 2015, 2017). First, built environments have many unique, sharp‐edged features that remain static during image capture and are minimally repeated over the landscape of interest, enabling the use of edge‐detection algorithms.…”
Section: Figurementioning
confidence: 99%
“…While approaches to estimating global rotation of each camera are well established [33]- [35], computing global translation priors is challenging, but recent studies have shown promising results [36], [37]. Moreover, incorporating extra information, such as sparse depth [30], vanishing points [38], GPS [39]- [42] and inertial data, has proven useful with the latter two common for photogrammetry and SLAM.…”
Section: Related Workmentioning
confidence: 99%
“…(3) search expansion candidates in _ g tcn; (4) execute candidate expansion in _ _ exp g mst ansion.…”
Section: Mst Expansion For Connection Network Enhancementmentioning
confidence: 99%